Pearl Millet Genotypes Irrigated with Brackish Water Under Different Levels of Agricultural Gypsum - Gêisa Araújo de Oliveira; Ossival Lolato Ribeiro; Gherman Garcia Leal de Araújo; Fleming Sena Campos; José Nildo Tabosa; Amadeu Regitano Neto; Thieres George Freire da Silva; Daniele Rebouças de Santana Loures; Glayciane Costa Gois (Grasses)
The aim was to evaluate the productivity, agronomic characteristics, and chemical and mineral composition of pearl millet genotypes irrigated with brackish water under the application of agricultural gypsum in two cuts. The experiment was a randomized block design in a 4 (gypsum levels—0, 2, 4, and 8 ton ha−1 applied on the surface) × 3 (pearl millet genotypes—ADR 300, BRS 1501, and IPA BULK 1BF) factorial arrangement, with three replications, irrigated with high brackish water and low sodium. Agricultural gypsum had no significant effect on productivity, agronomic characteristics, and chemical and mineral composition (p > 0.05). In the first cut, higher mean values were found for the percentage of panicle, crude protein, ether extract, in vitro dry matter digestibility, calcium, sulfur, and manganese (p < 0.05). For the second cut, higher results were observed for green matter productivity, dry matter productivity, water use efficiency, stem percentage, stem diameter, average leaf size, panicle size, acid detergent fiber, lignin, cellulose, total carbohydrates, potassium, and copper (p < 0.05). IPA Bulk 1 BF showed a larger panicle size in both cuts (p < 0.05). The evaluated pearl millet genotypes showed desirable agronomic characteristics and tolerance to irrigation with brackish water regardless of gypsum application, thus they are indicated for cultivation in the semi-arid regions.